1990
DOI: 10.1111/j.1540-6261.1990.tb05093.x
|View full text |Cite
|
Sign up to set email alerts
|

The Shelf Registration of Debt and Self Selection Bias

Abstract: Prior studies report lower issue costs for shelf registered debt and conclude that the benefits of increased underwriter competition can be realized by those firms using this registration procedure. This study re‐examines the purported superiority of issuing debt via shelf registration, and finds that the savings in issue costs displayed by earlier studies can be attributed to a self selection bias and not the method of registration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…None of these papers explicitly examines the pricing effect of a firm's loyalty to its bank. Several papers analyze the early effects of shelf registration in lowering underwriting fees and the cost of offerings (see Kidwell et al, 1987;Allen et al, 1990;Denis, 1991). Consistent with this evidence, we find that shelf-registered common stock offers have lower fees.…”
Section: Introductionsupporting
confidence: 84%
“…None of these papers explicitly examines the pricing effect of a firm's loyalty to its bank. Several papers analyze the early effects of shelf registration in lowering underwriting fees and the cost of offerings (see Kidwell et al, 1987;Allen et al, 1990;Denis, 1991). Consistent with this evidence, we find that shelf-registered common stock offers have lower fees.…”
Section: Introductionsupporting
confidence: 84%
“…A number of studies have examined the determinants of the at-issue yield spread, which is an increasing function of the issue costs (the at-issue yield is measured by equating the net proceeds, after deducting the issue costs, with the present value of the coupon and principal payments). Allen, Lamy and Thompson (1990), Datta, Iskandar-Datta and Patel (1999), as well as other studies, have documented that the at-issue yield spread is negatively related to credit rating and positively related to bond maturity. As issue costs are an important determinant of the at-issue yield spread, these findings imply similar relations for the issue costs.…”
Section: Prior Researchmentioning
confidence: 80%
“…We use SDC to determine which offerings are shelf registered. Several studies have shown that shelf registration has a negative effect on underwriting spreads and the cost of issuing equity (Kidwell, Marr, and Thompson, 1987;Allen, Lamy, and Thompson, 1990;Denis, 1991;Burch, Nanda, and Warther, 2005). We collect data on the amount of secondary shares in the offering from SDC.…”
Section: Underwriter Returnsmentioning
confidence: 99%
“…Shelf registration is only available for larger offerings, and reputable underwriters may desire shelf registered offerings due to their lower placement costs(Kidwell, Marr, and Thompson, 1987;Allen, Lamy, and Thompson, 1990;Denis, 1991).…”
mentioning
confidence: 99%